Analysis and implementation of minimal resource allocation networks (MRAN) for real-time applications - Tan, Kok Leong. (2008)
This thesis presents the theoretical and experimental analysis of computational complexity and performance evaluation of minimal resources allocation network (MRAN) from a real-time implementation perspective. MRAN is a sequential learning network and has the same structure as a radial basis function (RBF) network.